Perceptions of Indonesian Language Teachers Regarding the Application of Project-Based Learning Models at SMA Negeri 2 Siak Hulu - Devita Rahmawati Putri; Desi Sukenti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study aims to describe Indonesian language teachers’ perceptions of the implementation of Project-Based Learning at SMA Negeri 2 Siak Hulu. This research employed a qualitative approach with a phenomenological method to explore teachers’ experiences and perspectives in implementing Project-Based Learning. The participants consisted of five Indonesian Language teachers selected as informants. Data were collected through in-depth interviews and analyzed using thematic analysis, which involved data reduction, data display, and conclusion drawing. The findings indicate that teachers generally have positive perceptions of the implementation of Project-Based Learning. Initially, the model was perceived as challenging because it required thorough preparation and more complex classroom management. However, teachers acknowledged that Project-Based Learning fosters a more active learning environment and enhances students’ direct engagement in the learning process. They understood Project-Based Learning as a student-centered model in which students act as the main learning subjects, while teachers function as facilitators. Theoretically, this study contributes to the enrichment of phenomenological perspectives on teachers’ perceptions in the context of Indonesian Language learning and provides empirical support for the relevance of Project-Based Learning in improving instructional quality. Overall, Project-Based Learning is considered relevant and effective in enhancing the quality of Indonesian Language learning.